Validation of the Coping with Stress Self-Efficacy Scale in university students - Pereyra Girardi, Carolina Iris (2019)
The aim of this study is to examine evidence of content and face validity, construct validity, the internal consistency of the dimensions that compose the instrument, and concurrent validity. The sample included 333 students from a private Argentine university. Content and face validity was carried out by expert judges and a pilot test. Subsequently, a confirmatory factor analysis was carried out, comparing two factor models of first and second order. The results showed a proper adjustment of the first-order factor model, adequate internal consistency and evidence of concurrent validity. These results are discussed using the two dominant conceptions of self-efficacy.